1999
DOI: 10.1080/07328309908544058
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Synthesis of Several 2'-O-, 3'-O-Glycosylated Diosgenyl β-D-Glucopyranosides

Abstract: Six T-O-, 3'-O-glycosylated diosgenyl p-D-glucopyranosides (4-9), which have a typical structural pattern of diosgenyl saponins, were synthesized; their synthetic routes are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 13 publications
0
4
0
Order By: Relevance
“…Although both the aglycone and the carbohydrate moieties are required for the exhibition of their antitumor activity, the exact role of the carbohydrate moiety remains unclear. Thus, with target six compounds in hand, the cytotoxicity of the saponins was evaluated [24,[30][31][32][33]. The group of steroidal saponins exhibited a marked structure-dependent growth inhibitory activity against the human hepatocellular carcinoma (HepG2) cells (Table1), which supported that the saccharide group increased the cytotoxicity of trillin, especially for rhamnose.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Although both the aglycone and the carbohydrate moieties are required for the exhibition of their antitumor activity, the exact role of the carbohydrate moiety remains unclear. Thus, with target six compounds in hand, the cytotoxicity of the saponins was evaluated [24,[30][31][32][33]. The group of steroidal saponins exhibited a marked structure-dependent growth inhibitory activity against the human hepatocellular carcinoma (HepG2) cells (Table1), which supported that the saccharide group increased the cytotoxicity of trillin, especially for rhamnose.…”
Section: Resultsmentioning
confidence: 90%
“…High selectivity was observed on the pivaloylation of trillin under pivaloyl chloride (PivCl) in CH2Cl2/pyridine (3:1) solution affording the 3,6-di-Pivprotected diol 7 in 80% yield [23]. Glycosylation of diol 7 with 2,3,4-tri-O-benzoyl-α-L-rhamnopyranosyl trichloroacetimidate 8 [24] (1.2 equiv, -60 ℃) under the promotion of trimethylsilyl trifluoromethanesulfonate (TMSOTf) (0.2 equiv) gave the 2-O-glycosylated product 9 and 2,4-di-O-glycosylated product 10 in 50% and 32% yields, respectively. The presence of an acyl group at the 2-OH position of a sugar donor locks the newly formed glycosidic linkage in the 1,2-trans configuration [24].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, the carbohydrate subunits attached covalently to the backbone of spirostane saponins play an important role for its bioactivities [18][19][20] . During the previous research in our group, two spirostane saponins(A and B) [21,22] have been isolated from the Chinese medicinal plant Disporopsispernyi Diels (Fig.1) and the results of their anti-cancer activities showed good inhibitory activities against human leukemia cell line HL60(with IC 50 values of 9.3 and 6.1 μmol/L, respectively). These results revealed that the sugar Fig.1 Structures of spirostanic saponins A and B isolated from D. pernyi Diels moieties might be the key pharmacophore for the anti-cancer activities of spirostanic saponins [23] .…”
Section: Introductionmentioning
confidence: 98%